2016
DOI: 10.1111/ene.13066
|View full text |Cite
|
Sign up to set email alerts
|

Migraine is associated with better cognition in the middle‐aged and elderly: the Rotterdam Study

Abstract: Migraineurs, particularly migraineurs with aura, tend to score higher in cognition tests than non-migraineurs. More studies are needed to corroborate these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 48 publications
3
39
0
Order By: Relevance
“…Previous studies found that patients with migraine showed normal range of performance on both the MMSE [39] and MoCA [40]. Similarly, none were excluded due to abnormal performance on screening tests among migraineurs in this study.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies found that patients with migraine showed normal range of performance on both the MMSE [39] and MoCA [40]. Similarly, none were excluded due to abnormal performance on screening tests among migraineurs in this study.…”
Section: Discussionmentioning
confidence: 94%
“…Some studies suggest that migraineurs have subtle interictal cognitive abnormalities aligning with attentional deficits [911]. Some studies have reported improved performance [12]. Some longitudinal studies have suggested fewer dysfunctions in the Mini Mental State Examination (MMSE) and executive functions in migraineurs.…”
Section: Introductionmentioning
confidence: 99%
“…Neuromuscular disorders , trauma , neuro‐inflammation , headache and more general neurological topics complete the 2016 spectrum of the Journal's purview.…”
mentioning
confidence: 99%
“…Neuromuscular disorders , trauma [214,215], neuro-inflammation [216][217][218][219][220][221][222][223], headache [224][225][226][227][228][229][230][231] and more general neurological topics [232][233][234][235][236][237][238][239][240][241][242][243][244][245][246][247][248]…”
mentioning
confidence: 99%